The impact of fairtrade and other sustainability practices on cocoa farmers’ income of in Guayas and Manabi provinces, Ecuador - Celi Garofalo, Stefania (SLU/Dept. of Economics, 2020)
Voluntary sustainability standards on the one side, and, sustainable sourcing practices on the other side, are two favored ways of the cocoa industry for a more effective, social and environmental friendly value chains. But how well do these two kinds of sustainability schemes improve the cocoa farmers’ income? This thesis investigates the major factors affecting the income among cocoa farmers certified under Fairtrade and Fair for life, and non-certified cocoa farmers participating in Olam’s own sustainability program in the provinces of Guayas and Manabi, in the coastal region of Ecuador. The analysis uses survey data gathered through field interviews with a sample of each participating group during the end of the main crop period March-April 2019. The first part of the anlysis consist of multinomial probit regressions to understand what motivates a farmer to choose a program or not. The results identify that a male household is more likely to choose fair trade programs while for Olam younger farmers increases the probability to join their program. Larger farms are more likely to join Olam, while for Fairtrade this decreases the probability to join the program. Farmers with only cocoa monocultures are less likely to choose Olam. The regression model shows that income increases with accumulated program experience, larger cocoa farms, livelihood diversification, participation in training, yield, and farming experience. Minimum floor prices increase the income to FT and FL, meanwhile monetary premiums increase income for farmers belonging to Olam. Different results among the groups suggest that there is a need for better harmonization of sustainability practices, if sustainable practices will be implemented, between schemes to benefit farmers incomes.